Antioxidant and antibacterial activity of extract and phases from stems of Spartium junceum L. growing in Algeria - Natalizia Miceli,; Giovanna Ginestra,; Zineb Maameri,; Carlo Bisignano,; Francesco Cacciola,; Margita Utczas,; Luigi Mondello,; Sirajudheen Anwar,; Samir Benayache,; Damila Zama,; Fadila Benayache,; Maria Fernanda Taviano, (International Journal of Phytomedicine, 2016)
This work aimed to evaluate the antioxidant and antibacterial activities of the hydroalcoholic (80% methanol) extract and n-hexane (n-Hex), chloroform (Chl), ethyl acetate (EtAc), and n-butanol (n-But) phases from Spartium junceum L. stems collected inAlgeria. Preliminary phytochemical investigations on phenolic compounds have been carried out. The total phenolic content, spectrophotometrically determined, ranged from 71.8095 ± 3.7136 mg GAE/g (extract) to 0.0582 ± 0.0106 mg GAE/g (n-Hex). By HPLC-PDA analysis flavonoids (flavone derivatives), p-hydroxybenzoic acid, p-hydroxycinnamic acid, and cinnamic acid derivatives were identified both in the extract and phases. S. junceum extract showed a noticeable free radical scavenging effect in the DPPH test (IC50 = 0.6833 ± 0.0240 mg/mL), mild reducing power, and strong chelating activity (IC50 = 0.2292 ± 0.0138 mg/mL). Among the phases, n-But displayed the best effect both in the DPPH test and reducing power assay, whereas n-Hex resulted the most active in the ferrous ions chelating activity assay. A positive relationship between DPPH radical scavenging activity and total phenolic content was found. Both the extract and phases exhibited antimicrobial activity against Gram-positive bacteria only. Staphylococcus aureus ATCC 6538 was the most susceptible strain (MIC range: 15.60-250.00 µg/mL), and the Chl phase showed the greatest efficacy. S. junceum extract resulted non-toxic against Artemia salina. The obtained results demonstrate the potential of S. junceum stems as safe sources of natural antioxidant and antimicrobial compounds.